Pengaruh Substitusi Tepung Mocaf terhadap Kualitas Organoleptik Kulit Pastel - Nuari Sulam Sari; Annis Kandriasari; Cucu Cahyana (Pusat Riset dan Inovasi Nasional, 2024)
This study aimed to analyze the organoleptic quality of pastel skins with mocaf flour substitution. The study took place at the Food Processing Laboratory of the Culinary Education Study Program at Jakarta State University from January 2024 to March 2024, using experimental methods. The study samples were pastel skins with mocaf flour substitutions at 20%, 30%, and 40%. The experimental method involved testing the organoleptic quality by 3 limited panelist using a 5-point hedonic scale. The organoleptic test results assessed by panelist showed that pastels with 40% mocaf flour substitution received the highest ratings for skin color, skin surface texture, crispness, thinness, aroma, skin flavor, and overall flavor, while pastels with 20% mocaf flour substitution received the highest ratings for content. Descriptive test of the organoleptic quality recommended pastel products with a 40% mocaf flour substitution.